150 Ans de gravure en Belgique. - Rouir, Eugène; Liebaers, Herman (Bruxelles : CGER ( Caisse Generale d'Epargne et de retraite) Bruxelles, 1980)
Alechinsky, Pierre ; Barzin, Michel ; Baugniet, M.L. ; Belgeonne, Gabriel ; Benon, Jean-Pierre ; van den Berghe, Frits ; Bertrand, Gaston ; Billoin, Ch. ; de Bolle, Francis ; Bonvoisin, Joseph ; Boonen, Jacques ; Boulenger, Hippolyte ; De Braekeleer, Henri ; Brocas, Maurice ; De Bruycker, Jules ; Buisseret, Louis ; Caille, Pierre ; Cantre, Jan Frans ; Carcan, René Marcel ; Carte, Anto ; Charlier, Guillaume ; Cobbaert, Jan ; Collet, Louis ; Comhaire, George ; De Coninck, Roger ; Crommelynck, Robert ; Dacos, Guy-Henri ; Dechene, Jean ; Delhez, Victor ; Devolder, Roland ; Dewint, Roger ; Dille, Frans ; Dols, Jean ; Donnay, Auguste ; Donnay, Jean ; Duyts, Gustaaf Den ; Ensor, James ; Evenepoel, Henri ; Folon, Jean-Michel ; Fourmois, Théodore ; Gaudaen, G. ; Gorus, Jacques ; De Grave, Jean-Jacques ; Haccuria, Maurice ; Haert, Henri Van der ; Hamesse, Adolphe-Jean ; Heerbrandt, Henri ; Heintz, Richard ; Hendrikckx, J. ; Herckenrath, Anbtton ; Hoorne, Emiel ; Hougardy, E. ; Hoydonck, R. ; Humblet, Theo ; Jespers, Floris ; Khnopff, Fernand ; Laermans, Eugene ; Lafineur, M. ; Langaskens, Maurice ; Lauters, Paul ; Lemmen, George ; Leonard, Maurice ; Leys, Henri ; Linnig, J. ; Linnig, Willem Jr. ; Lismonde ; Lyr, Claude ; Madou, Jean-Baptiste ; Maes, Karel ; Mambour, August ; Marchoul, Gustave Fr. ; Marechal, F. ; Masereel, Frans ; Mels, René ; Mertens, Charles ; Minnaert, Frans ; Minne, George ; Minne, Joris ; Peeters, J. ; Peire, Luc ; Rassenfosse, André Louis Armand ; Rops, Félicien ; Van Rysselberghe, Theo ; Schaefels, Hendrik-Frans ; Schmetz, R. ; Servaes, Albert ; Simonau, G. ; De Smet, Gust ; Smits, Jakob ; Spilliaert, Léon ; Stevo, Jean ; Stobbaerts, Jean-Baptiste (Jan) ; Van Straten, Henri ; Stroobant, François ; Thomas, Rover Julama ; etc.
Frans
boek
Keywords: België